Johnny Cash international : how and why fans love the man in black - Hinds, Michael; Silverman, Jonathan, 1965- (Fandom & culture., 2020)
"How the world shows it loves Johnny Cash:: a Brazilian records "Hurt" and posts it to YouTube;an elderly shopkeeper in Northern Ireland plays Johnny Cash every day on his tape recorder ; a young man in Tomb, a farm town in southern Norway, sports a Johnny Cash tattoo; a woman in the Netherlands maintains the Johnny Cash Infocenter, an exhaustive resource of Johnny Cash materials worldwide--and gets to wear June Carter's clothing and sleep in Johnny Cash's bedroom. One might have suspected that Johnny Cash's appeal was universal, given his nonstop touring schedule for more than 40 years. But the breadth-and nuance-of his appeal worldwide is stunning, as is the way in which his fans have sought both to further that appeal as well as protect his legacy. International Cash: How the World Loves the Man in Black explores the nature of Johnny Cash's appeal worldwide from the fan perspective, explaining what the worldwide love of the artist tells us about him, the world, the United States, and the nature of fandom. It's also a series of stories about technology and authenticity, as a world easily navigated by the Internet is also one that conceives authenticity as a type of commodity easily displayed. Different eras of technology have also produced different fan behaviours and activities, and they are represented in continuity with one another here. There are Cash superfans who travel extensively to trail Cash's life and perform in homage to him, but there is also another population of Cash fans who express themselves more discreetly, often online. There they are often expressing their love for Cash in uncertain spaces, forums where there are no guarantees that everyone feels the same way as themselves. Here Cash is seen as somebody not only worth admiring, but worth fighting for, and this book shows that Cash fandom is a more active field of politics and commitment than might routinely be assumed"--